Upaya Mengembangkan Kemampuan Siswa Memahami Pembelajaran Pendidikan Agama Islam dan Budi Pekerti pada Materi Pernikahan Melalui Model Inkuiri pada Siswa Kelas XI DKV 2 SMKN 1 Kota Bengkulu Semester I Tahun Pelajaran 2024/2025 - Sihamli (Yayasan Darusssalam Bengkulu, 2025)
This study aims to improve the development of students' ability to understand Islamic religious education and character education on marriage material through an inquiry model for class XI DKV 2 SMKN 1 Bengkulu City students in the first semester of the 2024/2025 academic year. This research is a Classroom Action Research (CAR). Action research is intended to find the right action format in order to improve the program and quality of learning. This research focuses on efforts to change current real conditions towards expected conditions (improvement oriented). This CAR is carried out to develop students' ability to understand Islamic religious education and character education on marriage material through an inquiry model for class XI DKV 2 SMKN 1 Bengkulu City students. In this classroom action research, it refers to the research implementation process proposed by Kemmis and Mc Taggart (in Suyatno, 2009: 21) which includes carrying out planning, acting, observing, and reflecting. The sample in this study were 26 students of Class XI DKV 2 SMKN 1 Bengkulu City, Bengkulu Province. The ability of class XI DKV 2 students of SMKN 1 Bengkulu City in the 2024/2025 academic year in understanding marriage. The results of the study on the use of the inquiry model in Islamic Religious Education subjects in an effort to improve the achievement of class XI DKV 2 students of SMKN 1 Bengkulu City are when learning outcomes are stated to have increased where student learning outcomes in the pre-action phase have an average value of 69.5. in cycle I got an average score of 79 while KKTP was 75. Before the action or in the pre-action phase. Only 11 students were declared to have completed PAI learning. and in cycle II it increased to 100% This study focuses primarily on improving student learning achievement, and the results of the study resulted in an increase in student learning achievement using the inquiry model.